2013
DOI: 10.1111/ipd.12026
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators associated with dental erosion among Jordanian school children aged 12–14 years of age

Abstract: Dental erosion is a multifactorial condition in which mouth dryness, vomiting, cortisol inhaler use, keeping soft drinks in the mouth, drinking beverages at bed time, consumption of lemon, sour candies, and having confectionary as snacks are risk indicators, and area of residence are all potential factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 39 publications
6
63
1
4
Order By: Relevance
“…Hamasha et al (28), in his study in Jordanian school children aged 12-14 years found that frequent consumption of lemon was an important risk indicator for dental erosion. Various studies have identified consumption of lemon drinks as an important risk indicator for development of dental erosion due to its acidic contents (citric acid) (10,12).…”
Section: Discussionmentioning
confidence: 97%
“…Hamasha et al (28), in his study in Jordanian school children aged 12-14 years found that frequent consumption of lemon was an important risk indicator for dental erosion. Various studies have identified consumption of lemon drinks as an important risk indicator for development of dental erosion due to its acidic contents (citric acid) (10,12).…”
Section: Discussionmentioning
confidence: 97%
“…The relation of brushing technique and brushing force with the presence of cervical lesions has been confirmed in a number of studies (11,12). In addition, dietary factors such as consumption of lemon, citrus fruit, cola-flavored soft drinks, and citrus-flavored drinks have been implicated in the development of cervical lesions (13)(14)(15). Epidemiologic studies indicate that children attending special needs schools frequently have poor oral health (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This fact reinforces the idea that pH is just one of many factors to be considered in enamel erosion. 10 …”
Section: Discussionmentioning
confidence: 99%